Clinical, functional, and computed tomography findings in a cohort of patients with neuroendocrine cell hyperplasia of infancy. Issue 6 (23rd February 2021) - Balinotti, Juan E.; Maffey, Alberto; Colom, Alejandro; Roldán, Oscar; Díaz, Walter; Medín, Martín; Racimo, Mariano; Teper, Alejandro
Abstract: Introduction: Neuroendocrine cell hyperplasia of infancy (NEHI) is one of the most common interstitial lung diseases in children. Both the etiology and pathophysiological mechanisms of the disease are still unknown. Prognosis is usually favorable; however, there are significant morbidities during the early years of life. Objective: To describe the clinical course, infant pulmonary function tests and computed tomography (CT) findings in a cohort of patients with NEHI in Argentina. Methods: This is a observational multicenter cohort study of children diagnosed with NEHI between 2011 and 2020. Results: Twenty patients participated in this study. The median age of onset of symptoms was 3 months and the median age at diagnosis was 6 months. The most common clinical presentation was tachypnea, retractions and hypoxemia. The chest CT findings showed central ground glass opacities and air trapping. Infant pulmonary function tests revealed an obstructive pattern in 75% of the cases (10/12). Most patients (75%) required home oxygen therapy for 17 months (interquartile range 12–25). In 85% of them, tachypnea and hypoxemia spontaneously resolved between the second and third years of life. Conclusion: In this cohort, the first symptoms appeared during the early months of life. The typical clinical, CT, and functional findings allowed the diagnosis without the need of a lung biopsy. Although most patients required home oxygen therapy, they showed a favorable evolution.